2012
DOI: 10.3140/bull.geosci.1225
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomy of Cambrian (Stage 3/4) sponges from Yunnan (South China)

Abstract: Sponges are one of the major faunistic components of the Burgess Shale-type fossil Lagerstätte of Chengjiang (Cambrian Stage 3, South China). Although pyritization is often invoked as a key process linked to the early diagenetic preservation in the Chengjiang Fauna, the unweathered specimens analyzed lack evidence of pyrite. Energy dispersive X-ray (EDX) analyses of these specimens show a robust and continuous film of organic carbon. Most of the Chengjiang sponges underwent extensive weathering and diagenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…A comprehensive analysis of the effects of weathering on the Chengjiang fossils was undertaken by Forchielli et al (2014), who characterized the elemental composition of fossils and the mineralogic and chemical composition of the host mudstones across a weathering gradient. The results of this study confirmed earlier suggestions (Hu, 2005;Forchielli et al, 2012) that pyritization in Chengjiang fossils was limited to discrete anatomical aspects, and verified the dominance of carbonaceous preservation in unweathered specimens. With weathering, Chengjiang fossils were shown to progressively lose carbon and to acquire coatings of Fe-oxides derived from the oxidation of pyrite in the enclosing mudstones (as evidenced by the loss of S) and resulting from the redistribution of Fe along voids and cracks, including those associated with Burgess Shaletype fossils (Forchielli et al, 2014).…”
Section: ! Auxiliary Mineralization Of Selected Soft Tissuessupporting
confidence: 91%
“…A comprehensive analysis of the effects of weathering on the Chengjiang fossils was undertaken by Forchielli et al (2014), who characterized the elemental composition of fossils and the mineralogic and chemical composition of the host mudstones across a weathering gradient. The results of this study confirmed earlier suggestions (Hu, 2005;Forchielli et al, 2012) that pyritization in Chengjiang fossils was limited to discrete anatomical aspects, and verified the dominance of carbonaceous preservation in unweathered specimens. With weathering, Chengjiang fossils were shown to progressively lose carbon and to acquire coatings of Fe-oxides derived from the oxidation of pyrite in the enclosing mudstones (as evidenced by the loss of S) and resulting from the redistribution of Fe along voids and cracks, including those associated with Burgess Shaletype fossils (Forchielli et al, 2014).…”
Section: ! Auxiliary Mineralization Of Selected Soft Tissuessupporting
confidence: 91%
“…Although it is impossible to confirm the original compositions based on the current material, the impressions were probably produced by mineralized tissues. Silica and carbonates, both commonly utilized in sponge skeletal construction, are often diagenetically dissolved in Chengjiang fossils (e.g., Forchielli et al, 2012).
Figure 4.Raman spectra measured from Vauxia leioia n.
…”
Section: Discussionmentioning
confidence: 99%
“…The oxidation of early-formed iron pyrite would produce a low pH environment and small amounts of H 2 SO 4 on and perhaps around the carcass. Thus, original biominerals have been dissolved 28 (but see 31 , who report un-weathered sponge spicules showing a robust carbon film and no pyrite), and it is not possible to determine the original composition of the spines.…”
Section: Discussionmentioning
confidence: 99%